King of Shadows - Cooper, Susan, 1935- (New York : Margaret K. McElderry Books, 1999)
While in London as part of an all-boy acting company preparing to perform in a replica of the famous Globe Theatre, Nat Field suddenly finds himself transported back to 1599 and performing in the original theater under the tutelage of Shakespeare himself.
Accelerated Reader AR